PARADIGMA PEMIKIRAN HUKUM ISLAM DALAM KEILMUAN MODERN - Arfah Ibrahim (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2013)
The modern era has led fiqh (Islamic law) on the problematic position anddilemma. Fiqh is not only difficult to solve various problems and social issuesfacing but also still stutter defines selfhood, especially in the context offormulating a viable legal method used to solve various problems. In view ofCoulson, the problem is what is in the cause of conflict and tension betweentheory and practice in the history of research and application of Islamic law.Indonesian Islamic legal thought in an attempt to deliver a maximum of scholarsschools of law in line with the culture of the Indonesian Islamic community.Therefore, this product can be applied to legal thought, either philosophical,juridical and sociological-cultural formal. One of the problems with thedevelopment of Islamic legal irrelevance and thought he was assessed in respectof human civilization as a static law is the lack of use of scientific methodology asdeveloped in the West. By him that the historical approach, socio-cultural,philosophical and theological-scientific approach is a solution to the Islamizationof modern scientific paradigm repertoire of classical Islamic legal methodology.So the new paradigm of Islamic law is the outcome of these approaches, namelythe paradigm that sees Islamic law in an integrated manner, both as a normativeinstitutions that prioritizes basic values of Islamic legal certainty as well associological philosophy that prioritizes fundamental values of justice and truth